NPS MedicineWise: 20 years of change - Weekes, Lynn Maria (J Pharm Policy Pract, 2018)
The cost and potential harms of medicines and other health technologies are issues of concern for governments and third party payers of health care. Various means have been demonstrated to promote appropriate evidence-based use of these technologies as a way to reduce waste and unintended variation. Since 1998, Australia has had a national organisation responsible for large scale programs to address safe, effective and cost effective use of health technologies. This article reviews 20 years of experience for NPS MedicineWise (NPS). NPS provides evidence-based information to health professionals and consumers using interventions that have been shown to be effective. A mix of academic detailing, audit and feedback and interactive learning is built into national programs designed to improve the use of medicines and medical tests. The target audiences have typically been general practitioners, pharmacists and nurses in primary care. Consumer programs, including mass media campaigns have supported the work with health professionals. NPS receives most of its income from the Australian Government and in return it is required to show saving for the Pharmaceutical Benefits Scheme and the Medical Benefits Schedule. Since 1998, total savings of AUD 1096.62 million have been demonstrated. In addition, changes in knowledge and attitudes, changes in prescribing and test ordering behaviours and improvements in health outcomes have been shown through annual evaluations.